Educational Responses to Students With High Abilities From the Parental Perspective - Rodríguez-Naveiras, Elena; Cadenas, María; Borges, África; Valadez, Dolores (Frontiers in Psychology, 2019)
Students who have high abilities demand educational responses, both inside and outside of the classroom. The best type of educational strategy depends on the characteristics of the students, the school, the educational system, and the country. For this reason, the level of attention paid to high-ability students can vary across nations. To guarantee the efficacy of programs that are implemented both inside and outside of school, it is essential to offer to these students the support that they need. The students’ parents are a fundamental component of this scenario. This study evaluates the educational support provided to students with high abilities from a parental perspective. This study’s aim is to evaluate the opinions that parents in several countries hold about the educational responses to gifted students, as well as to compare the types of strategies implemented in these countries’ respective educational systems. Parents of students with high abilities completed an ad hoc online questionnaire that was designed to identify the types of educational responses, the students’ participation in enrichment programs (inside and outside of school), the parents’ level of satisfaction with these programs, and any difficulties or problems that occurred. A mixed methodology was used, with both quantitative and qualitative survey questions. ALCESTE software was used to analyze the open-ended (qualitative) questions. This research, which was directed by the Network of Research, Intervention and Evaluation in High Intellectual Abilities, focused on three countries: Mexico, Argentina, and Spain. Descriptive analysis were carried out for analyzing the questions related with the educational support and demographic information. Qualitative analysis were used to analyze open-ended questions. The results provide evidence on which types of educational responses are being implemented in those countries, how they are being used, and whether they offer appropriate support for the needs of high-ability students.